The Impact of Dental Health Service Quality and Innovative Entrepreneurial Orientation on Business Performance in Dental Clinics: A Resource-Based View Framework - Nina Agustin Chrystinasari; Murpin Josua Sembiring; David Sukardi Kodrat (Bulletin of Community Engagement, 2026)
This study investigates the impact of dental healthcare service quality and innovative entrepreneurial orientation on the business performance of dental clinics in the Greater Malang region. A quantitative research design was applied through a survey involving 39 respondents, including clinic managers, dentists, and professionals knowledgeable about clinic management and operations. The collected data were analyzed using Structural Equation Modeling (SEM) to evaluate the relationships among the study variables systematically and accurately. The findings reveal that dental service quality significantly contributes to improving clinic business performance through service structure, service processes, and patient outcomes. Better service quality enhances patient satisfaction, strengthens customer loyalty, and supports sustainable business growth. Furthermore, innovative entrepreneurial orientation was found to positively influence clinic performance. This orientation is reflected in the clinics’ ability to develop innovations, respond proactively to market changes, and take strategic risks in a competitive healthcare environment. The study also highlights that innovative entrepreneurship enables clinics to adapt their business strategies to the rapidly changing healthcare market. Innovation in both healthcare services and managerial practices helps clinics improve competitiveness and maintain long-term sustainability. Overall, the research emphasizes that combining high-quality dental services with innovative entrepreneurial practices plays a crucial role in optimizing business performance and sustaining competitive advantage in the dental healthcare industry.